The Role of Mast Cells in the Myocardial Infarction an Autopsy Report - Pakiş, Işıl; Akyıldız, Elif Ülker; Turan, Arzu Akçay; Karayel, Ferah; Ersoy, Gökhan; Kır, Muhammed Ziya (The Bulletin of Legal Medicine, 2008)
Mast cells, which include proteoglycan granules, originate from the bone marrow and are detectable in both peripheral blood and tissues. As in many other tissues, cardiac infarctions and inflammations precipitate mast cell degranulation. Mast cells and macrophages play an important part in the recovery process of mycardial infarction. In this study, autopsy records from the years 2003-2005 were reviewed 40 cases of myocardial infarction at different stages were selected randomly. 10 cases of trauma with lethal outcome and no detectable cardiac pathology were selected as the control group. Mast cells were stained selectively with Toluidine Blue. The relationship between the number of mast cells and the stage of myocardial infarction was assessed. There was a significant increase in number of mast cells in cases with transition to late stages of granulation tissue and fibrosis formation. These findings support the view that mast cells might play a role in cases of myocardial infarction in fibrosis tissue formation and remodeling of the extracellular matrix.Key words: Mast cells, myocardial infarction, fibrosis, autopsy
Keywords: mast cells; myocardial infarction; fibrosis; autopsy